PKPU AS AN ALTERNATIVE SOLUTION TO SETTLEMENT OF INDIVIDUAL DEBTORS' DEBT IN FINTECH LENDING SERVICES - Faqi, Ahmad Fachri; Jamila, Fadilla; Rai, Raga; Pappa, Erika (Awang Long Law Review, 2024)
The resolution of individual debtor debts in Fintech Lending Services has been regulated under POJK 10/2022. In addition to dispute resolution through district courts or alternative dispute resolution mechanisms, the PKPU mechanism is available to address the debt issues of individual debtors in Fintech Lending services. This study examines the resolution of individual debtor debts through the PKPU mechanism as a more equitable, expedient, and effective alternative. The research employs normative legal methods, utilizing secondary data such as legislation and relevant legal literature. Data collection is conducted through documentation and literature studies. The findings indicate that the debts of individual debtors in Fintech Lending services can be resolved through the PKPU mechanism, as such debts fall within the scope of Law No. 37/2004. However, the application of this mechanism faces challenges, such as the requirement for applications to be filed by an advocate and the condition that there must be a minimum of two creditors, which complicates matters for individual debtors. Moreover, Law No. 37/2004 has not fully protected individual debtors, as debt forgiveness or cancellation still depends on creditors' approval.